The Relationship Between Family Support and Stress Levels in Final Report Preparation Among Students - Sania, Launa Lutfi; Oktaviani, Sophia; Syahara, Dilla Adisty; Al Fiqri, Sulton; Amelia, Rin Rin (Yayasan Inspirasi El Burhani, 2024)
Introduction: Academic stress during the final year of study, particularly during the preparation of culminating reports or theses, is a well-documented phenomenon. Although family support is often posited as a protective factor, empirical evidence regarding its specific impact remains limited. This study addresses this gap by examining the relationship between perceived family support and stress levels among pharmacy students at STIKes Muhammadiyah Ciamis engaged in final report preparation. The research aims to provide a nuanced understanding of how family dynamics influence academic stress within this particular context. Objective: To examine the association between perceived family support and stress levels among final-semester students during final report preparation. Method: A cross-sectional quantitative study was conducted from March to May 2024 at STIKes Muhammadiyah Ciamis involving 33 final-semester Pharmacy students. Data were collected via a validated online questionnaire assessing family support (16 items) and stress levels (14 items) using a 4-point Likert scale. Data were analyzed using descriptive statistics and the Chi-square test with a significance level of p < 0.05. Results: Most respondents experiencing moderate to very severe stress reported having supportive families. However, statistical analysis showed no significant relationship between family support and stress levels (p = 0.177). Conclusion: There is no significant association between perceived family support and academic stress. These findings suggest that other internal and academic factors may play a greater role in influencing student stress during final report writing.